Self Discovery and Backpackers: A conceptual paper about liminal experience - Ting, Amanda (The international journal of religious tourism and pilgrimage, 2016)
Little is known about liminoid', the state of suspension'. However, every backpacker definitely passes through it, to journey from one transitional state of mind, to arrive at the next level of social status; Crossing the threshold between childhood to maturity, peace to war, singlehood to marriage and from being spiritually lost to found. Inspired by Victor Turner's (1969) significance of the betwixt and between' level which he named liminal, this paper aims to explore the process of backpackers' self-discovery by seeking the means of travel through states of cultural rituals, transcendental meditation, adventure and recreational activities. Findings in the literature suggest that these philosophical questions form the foundations which push young backpackers to embark on personal self-actualization journeys to destinations which they perceive to deliver a sense of inner-acceptance, whilst promoting spiritual divined growth, which therefore, elevate a backpacker's status in the perception of society.